PSYCHOSOCIAL SUPPORT CHALLENGES IN MATARAM WEST NUSA TENGGARA: Stakeholder Perspectives - Mujahidin Hasanul Bisri (SANGKÃ©P: Jurnal Kajian Sosial Keagamaan, 2023)
This study aims to identify challenges and obstacles in implementing psychosocial support programs by stakeholders in local communities in Mataram, West Nusa Tenggara (NTB). Qualitative research and purposive sampling were employed to select ten participants from three departments in Mataram. Interviews were conducted, data was observed and analyzed using ATLAS.ti. The study provides crucial insights into Mataram's context. The results showed that stakeholders face several challenges, including limited human resources in mental health, stigma against mental health, mismatch in program implementation, and lack of family support. The implications of this study are the importance of increasing the number and quality of human resources in mental health, involving families in patient care, improving coordination between relevant departments, and building collaboration between governments, non-governmental institutions, and communities. Recommendations based on the findings of this study are to increase public awareness about mental health, reduce stigma, allocate adequate funds, and develop consistent and sustainable psychosocial support programs. This research contributes to understanding the specific context in Mataram, NTB, and guides policies and practices addressing mental health problems in local communities.